Determinants of survival following pelvic exenteration for primary rectal cancer. Issue 10 (11th June 2015) - Radwan, R. W.; Jones, H. G.; Rawat, N.; Davies, M.; Evans, M. D.; Harris, D. A.; Beynon, J.; Swansea Pelvic Oncology Group; McGregor, A. D.; Morgan, A. R.; Freites, O.; Patel, B.; et al.
<x xml:space="preserve">Abstract</x> Background Pelvic exenteration is a potentially curative treatment for locally advanced primary rectal cancer. Previous studies have been limited by small sample sizes and heterogeneous data. A consecutive series of patients was studied to identify the clinicopathological determinants of survival. Methods All patients undergoing pelvic exenterative surgery for primary rectal cancer (1992–2014) at this hospital were analysed. The primary outcome measure was 5‐year overall survival. Secondary endpoints included length of hospital stay, complication rate, 30‐day mortality and disease recurrence rate. Statistical analysis was performed using Kaplan–Meier and Cox regression analysis. Results A total of 174 patients with a median age of 65 (range 31–90) years were included. Ninety‐six patients underwent posterior pelvic exenteration and 78 had total pelvic exenteration. Median follow‐up was 48 (range 1–229) months. Two patients (1·1 per cent) died within 30 days of surgery and 16·1 per cent returned to the operating theatre. The 5‐year survival rate following complete resection (R0) was 59·3 per cent. In univariable analysis, adverse survival was associated with advanced age (P = 0·003), metastatic disease (P = 0·001), pathological node status (P = 0·001), circumferential resection margin (P = 0·001), local recurrence (P = 0·015) and the need for neoadjuvant therapy (P = 0·039). Conclusion Pelvic exenteration is an aggressive treatment option with a high morbidity rate that provides favourable long‐term outcomes in patients with locally advanced primary rectal cancer.